2007
DOI: 10.1002/app.26528
|View full text |Cite
|
Sign up to set email alerts
|

Styrene–butadiene block copolymer with high cis‐1,4 microstructure

Abstract: ABSTRACT:The sequential block copolymerization of styrene (St) and butadiene (Bd) was carried out with an activated rare earth catalyst composed of catalyst neodymium tricarboxylate (Nd), cocatalyst Al(i-Bu) 3 (Al), and chlorinating agent (Cl). The microstructure, composition, and morphology of the copolymer were characterized by FTIR, 1 H NMR, 13 C NMR, and TEM. The results show that styrenebutadiene diblock copolymer with high cis-1,4 microstructure of butadiene units ( 97 mol %) was synthesized. The cis-sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…For example, the signals at 30.42 assignment to T 1 ‐S indicates the presence of the St‐ trans ‐1,4 BD sequence. No signals of St‐vinyl BD linkage in the vicinity of a chemical shift at 32.33 ppm are observed in the spectrum …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the signals at 30.42 assignment to T 1 ‐S indicates the presence of the St‐ trans ‐1,4 BD sequence. No signals of St‐vinyl BD linkage in the vicinity of a chemical shift at 32.33 ppm are observed in the spectrum …”
Section: Resultsmentioning
confidence: 98%
“…The spectrum of the copolymer sample displays typical signals of BD and St units inserted within the SBR polymer chain. The chemical shifts and the assignments of the 13 C NMR signals of the different monomer units are listed in Table for the aliphatic region . Table shows the constitutional monomeric units of the SBR copolymer for identification using the 13 C NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the existence of bulky substituents on the silicon atoms increases the thermal and hydrolytic stability of cyclodisilazanes. Therefore, phenylsubstituted cyclodisilazanes are expected to be introduced into the backbone of linear polysiloxane chains to synthesize thermally resistant elastomers [8,9]. An important goal in this area is the synthesis of cyclodisilazane monomer [10e16] with a feasible structure.…”
Section: Introductionmentioning
confidence: 99%
“…The first paper on the use of lanthanides for conjugated dienes polymerization originated in 1964 . There are many publications on the neodymium‐based catalysts for synthesis of Nd–BR in laboratory or in industry . The large‐scale industrial production of BR by neodymium‐based catalyst was established in the early to mid 1980s, first by Anic/Eni and shortly after by Bayer .…”
Section: Introductionmentioning
confidence: 99%